Fructose-sorbitol ingestion provokes gastrointestinal symptoms in patients with eating disorders - Friesen, Noel (The WJG Press and Baishideng, 2009)
AIM: To evaluate gastrointestinal (GI) symptoms and breath hydrogen responses to oral fructose-sorbitol (F-S) and glucose challenges in eating disorder (ED) patients. METHODS: GI symptoms and hydrogen breath concentration were monitored in 26 female ED inpatients for 3 h, following ingestion of 50 g glucose on one day, and 25 g fructose/5 g sorbitol on the next day, after an overnight fast on each occasion. Responses to F-S were compared to those of 20 asymptomatic healthy females. RESULTS: F-S provoked GI symptoms in 15 ED patients and one healthy control (P < 0.05 ED vs control). Only one ED patient displayed symptom provocation to glucose (P < 0.01 vs F-S response). A greater symptom response was observed in ED patients with a body mass index (BMI) ≤ 17.5 kg/m(2) compared to those with a BMI > 17.5 kg/m(2) (P < 0.01). There were no differences in psychological scores, prevalence of functional GI disorders or breath hydrogen responses between patients with and without an F-S response. CONCLUSION: F-S, but not glucose, provokes GI symptoms in ED patients, predominantly those with low BMI. These findings are important in the dietary management of ED patients.